EKSISTENSI DEVELOPER GAME INDEPENDEN INDONESIA (Studi Kasus Eksistensi Developer Game Indepeden Agate Studio, Creacle Studio, dan Digital Happiness Dalam Perspektif Ekonomi Politik Komunikasi) - Ardian Indro Yuwono (Universitas Gadjah Mada, 2021)
This study aims to understand how Indonesian independent game developers strive to exist in the competitive game industry. This research uses case study method with a political economy approach based Vincent Mosco’s political economy of communication. The political economy aproach are commodification, spatialization and structuration. This research conclude how Creacle Studio, Agate Studio and Digital Happiness carry out various commodification, spatialization and structuration practices in maintaining their independent studios in the Indonesian video game industry. The three studios practice political economy in different ways to survive in the video game industry.